Kinetic analysis and structural studies of a high‐efficiency laccase from Cerrena sp. RSD1 - Meng‐Hsuan Wu; Cheng‐Chung Lee; An‐Shan Hsiao; Su‐May Yu; Andrew H.‐J. Wang; Tuan‐Hua David Ho (FEBS Open Bio, 2018)
A high‐efficiency laccase, DLac, was isolated from Cerrena sp. RSD1. The kinetic studies indicate that DLac is a diffusion‐limited enzyme. The crystal structure of DLac was determined to atomic resolution, and its overall structure shares high homology to monomeric laccases, but displays unique substrate‐binding loops from those in other laccases. The substrate‐binding residues with small side chain and the short substrate‐binding loop IV broaden the substrate‐binding cavity and may facilitate large substrate diffusion. Unlike highly glycosylated fungal laccases, the less‐glycosylated DLac contains one highly conserved glycosylation site at N432 and an unique glycosylation site at N468. The N‐glycans stabilize the substrate‐binding loops and the protein structure, and the first N‐acetylglucosamine is crucial for the catalytic efficiency. Additionally, a fivefold increase in protein yield is achieved via the submerged culture method for industrial applications. Database The atomic coordinates of the structure of DLac from Cerrena sp. RSD1 and structural factors have been deposited in the RCSB Protein Data Bank (PDB ID: 5Z1X).